2021
DOI: 10.3390/ijerph18168705
|View full text |Cite
|
Sign up to set email alerts
|

Coparenting and Mental Health in Families with Jailed Parents

Abstract: The number of families affected by parental incarceration in the United States has increased dramatically in the past three decades, with primarily negative implications for adult mental health and child and family well-being. Despite research documenting increased strain on coparenting relationships, less is known regarding the relation between adult mental health and coparenting quality. This study investigated coparenting in families with young children currently experiencing parental incarceration. In a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…The aforementioned is congruent with not perpetuating attachment injuries into the next generation. Prior research has documented that incarceration can be a form of dysfunction that can be detrimental to familial relationships [51–54, 82]. Previous research indicated justice‐involved couples and correlations with increased infidelity, lower relationship quality, and lower marriage rates [13, 19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned is congruent with not perpetuating attachment injuries into the next generation. Prior research has documented that incarceration can be a form of dysfunction that can be detrimental to familial relationships [51–54, 82]. Previous research indicated justice‐involved couples and correlations with increased infidelity, lower relationship quality, and lower marriage rates [13, 19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…The most noteworthy implication inherent in our findings is related to the mental health of the non-incarcerated, primary caregiver at home. An abundance of research has demonstrated that the caregivers remaining at home, most often biological mothers in the context of paternal incarceration, experience elevated mental health symptoms [ 84 ] and overall increased stress. Indeed, prior research has identified a direct association between caregiver anxiety, depression, and poor youth outcomes during PI [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…An abundance of research has demonstrated that the caregivers remaining at home, most often biological mothers in the context of paternal incarceration, experience elevated mental health symptoms [ 84 ] and overall increased stress. Indeed, prior research has identified a direct association between caregiver anxiety, depression, and poor youth outcomes during PI [ 84 , 85 ]. Our study adds to this literature and, to the best of our knowledge, is the first to demonstrate that stable caregiver mental health strongly mediates how youth with an imprisoned father fare in school.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coparenting can provide protective health factors, such as increasing the positive mood of children and increasing positive interactions among parenting alliances and improving children life outcomes (Loper et al, 2014; Tadros & Durante, 2021; Tadros, Durante, et al, 2021; Tadros, Fanning, et al, 2021). Conversely, a strained coparenting relationship during incarceration can bring about health risk factors such as increased stress due to family conflicts that arise from feelings of shame and anger or shared financial and intimacy burdens.…”
Section: Physical Health Effects Of Incarcerationmentioning
confidence: 99%